Evaluación de una formulación para la elaboración de suelas de caucho mediante la inclusión de cloropreno y parafinas cloradas en la empresa Croydon Colombia S.A (2020)
The objective of this project is to evaluate a formulation for the elaboration of rubber soles through the incorporation of chloroprene and chlorinated paraffins in the company Croydon Colombia SA, through mixtures that differ from the amount of synthetic rubber and chloro alkanes, evaluating their properties, In order to select the one with the most effective results for use on soles. Initially, the rubber sole currently manufactured in the company was characterized from the measurement of abrasion, elongation, tearing, tension, bending, hardness, density and adhesion with black and grey synthetic cut, determining the acceptance values required by the company and by the military reference NTMD-0090-A4 established by the Ministry of National Defense. Subsequent to this six formulations were developed for the manufacture of rubber soles, varying the proportions of chloroprene and chlorinated paraffins into three levels: 5, 10 and 15 PHR, evaluating the same eight properties of the first stage.